2001
DOI: 10.1177/152660280100800304
|View full text |Cite
|
Sign up to set email alerts
|

Failed AAA Endograft Exclusion Due to Type II Endoleak: Explant Analysis

Abstract: Serial imaging is a vital component of endograft surveillance, and persistent type II endoleaks that cannot be completely embolized endanger the longevity of the aneurysm exclusion. Explant analysis can play an important role in understanding the mechanisms of endograft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…25 Several clinical studies also have suggested that aneurysm growth and even rupture of excluded aneurysms, surgically or by stentgraft, can be caused by patent collateral pathways. 7,26,27 In the present study we demonstrated that a patent IMA at preoperative imaging was significantly associated with late collateral endoleak. Other groups made similar observations of preoperative branch vessel patency and increased rates of type II endoleak following EVAR.…”
Section: Discussionsupporting
confidence: 57%
“…25 Several clinical studies also have suggested that aneurysm growth and even rupture of excluded aneurysms, surgically or by stentgraft, can be caused by patent collateral pathways. 7,26,27 In the present study we demonstrated that a patent IMA at preoperative imaging was significantly associated with late collateral endoleak. Other groups made similar observations of preoperative branch vessel patency and increased rates of type II endoleak following EVAR.…”
Section: Discussionsupporting
confidence: 57%
“…One of these patients underwent multiple embolizations but had persistent aneurysm enlargement and required open conversion at 21 months. 23 Volumetric analysis of the remaining patients who underwent embolization (n ϭ 7) revealed a volume increase of ϩ14.2% at 6 months. Postembolization volume changes were small (ϩ0.9% when compared with pre-embolization volume), even 2 years after the intervention (Table V).…”
Section: Resultsmentioning
confidence: 97%
“…Although earlier reports allude to the benign nature of type II endoleaks, recent reports on aneurysm rupture question this perception. [11][12][13][14] Baum et al 15 reported their experience with translumbar aneurysm sac angiograms, and suggest that all type II endoleaks transmit systemic pressure; however, the exact distribution of pressure within the aneurysm sac and onto the aneurysm wall was inconsistent and unpredictable. Regardless, the optimal treatment of type II endoleaks remains controversial, and ranges from continued aneurysm surveillance, to endovascular repair with embolization with coils, glues, and thrombin or gelatin sponge (Gelfoam), to open surgical repair.…”
Section: Discussionmentioning
confidence: 99%